Teenagers From Outer Space: Contributos para uma genealogia dos fios que teceram a moda e o do-it-yourself em Portugal - Guerra, Paula (2022)
Fashion - in Portugal - remains somewhat remote in academic studies. Few are the investigations, of historical-social focus, that have addressed the importance of fashion in Portugal with the exception of the work of Cristina L. Duarte (2016). Seeking to address this relative omission, we propose a diachronic exercise - since the late 1970s - focused on the relationship between the do-it-yourself (DIY), the fashion manifested in urban (youth) cultures and the (post)-punk emphasizing a qualitative and ethnographic approach. This article aims, above all, clarify, analyze and reflect on the triad fashion, DIY and punk, trying to explain the metamorphosis that the DIY ethos and praxis have undergone since the mid-1970s (post-Carnation Revolution) to the present day. We prioritize, in this sense, the approach of the following axes: anti-fashion, punk, cosmopolitanism and inevitability of DIY in the late 1970s; fashion, (post)-punk, resistance and implementation of DIY in the 1980s; fashion commodification and punk aesthetics and the development of DIY in social movements and alternative lifestyles in the 1990s; fashion, DIY commodification, artistic production, ecological activism and slow fashion movements in the 2000s and beyond. Thus, through these four compass-axes, we add an empirical-conceptual path around the evolution of DIY and fashion in Portugal, embarking on a mnemonic tour, where we revisit shops, events, happenings, leisure spaces, actors and aesthetics; inquiring, in each of these topics, the threads with which DIY was sewn in view of the Barthesian principle that a variation of clothing is necessarily accompanied by a variation of the world and vice versa.